PEMODELAN ARUS KENDARAAN MENGGUNAKAN AGENT-BASED MODELING STUDI KASUS LALU LINTAS JALAN TUASAN MEDAN - simorangkir, risna; Reza Nur Afdal; Putri Harliana (PINTER : Jurnal Pendidikan Teknik Informatika dan Komputer, 2025)
Traffic congestion is a significant challenge in big cities such as Medan, especially on Jalan Tuasan which often experiences congestion during peak hours. This study aims to model the traffic flow at Jalan Tuasan intersection using Agent-Based Modeling (ABM) approach. This method allows the simulation of individual vehicle behavior as interacting agents in a dynamic system. Primary data was collected through direct observation for three days at three time spans (morning, afternoon, evening). The simulation results show that the implementation of traffic lights can improve the efficiency of vehicle movement, as seen from the increase in average speed and the reduction of potential conflicts at the intersection. This study proves that the ABM model is effective in evaluating micro and dynamic traffic management scenarios.